Membumikan Moderasi Beragama “Ikhtiar dalam Mewujudkan Masyarakat Cinta Damai” - Syarifudin Syarifudin; M. Khatami (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2022)
In early 2019, the Ministry of Religious Affairs through the National Working Meeting at the Sherton Hotel Jakarta issued three main taglines, namely religious moderation, community togetherness and data integration. One of the three taglines, namely religious moderation, is then systematically a leading program that frames all kinds of religious policies, which are based on the ideas and attitudes of washatiyatul Islam. Religious moderation is very important in religious and state life. For the Indonesian people, religion means we are Indonesian, and being Indonesian means we are religious. Religious moderation is a means for the realization of harmony, harmony, peace, and benefit in achieving common ideals towards a just Indonesia in prosperity. In line with the national ideals stated in Pancasila and the 1945 Constitution.